Workshop Penelitian Pendidikan pada KKG Gugus II Lubuk Besar: Educational Research Workshop in KKG Cluster II Lubuk Besar - Muhammad Eka Mardyansyah Simbolon; Vika Martahayu; Oktarina Oktarina; Dzihan Khilmi Ayu Firdausi; Karmila Sari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The pandemic has an impact on all lines of people's lives. The education sector has not been spared from the impact of the Covid-19 pandemic. Implementation of learning must make a lot of adjustments. It is necessary to increase and improve the implementation of learning in a pandemic situation through scientific research activities. However, educational actors, especially teachers, have had several obstacles in conducting research to improve the quality of learning during a pandemic. Through the Stimulus Community Partnership Program (PKMS), a workshop was held for 85 teachers who are members of the Group II Elementary School (SD) Teacher Working Group (KKG), Lubuk Besar District as a partner problem solving. The results of the N-Gain test on partner competence obtained a value of 0.35 (moderate). This workshop, which is held for service partners, can increase the competence of partners' knowledge about scientific research activities in order to improve the quality of learning during the current pandemic.